1996
DOI: 10.1111/j.1524-4725.1996.tb00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Improvement of Photoaged Skin with 50% Glycolic Acid A Double-Blind Vehicle-controlled Study

Abstract: The results of this study demonstrate that the application of 50% glycolic acid peels improves mild photoaging of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 9 publications
0
52
1
2
Order By: Relevance
“…It can also thin the stratum corneum and epidermis, as well as increase dermal collagen thickness. 145 GA is found in many skin creams and has been shown to modestly improve photodamage when used in this fashion. 183 GA can also increase sunburn cell formation and sensitivity to UV-induced erythema.…”
Section: Tertiary Therapiesmentioning
confidence: 99%
“…It can also thin the stratum corneum and epidermis, as well as increase dermal collagen thickness. 145 GA is found in many skin creams and has been shown to modestly improve photodamage when used in this fashion. 183 GA can also increase sunburn cell formation and sensitivity to UV-induced erythema.…”
Section: Tertiary Therapiesmentioning
confidence: 99%
“…Chemical peels to improve irregular pigmentation have been performed on the nonfacial area using glycolic acid, 19 TCA, 20 Jessner's solution, 21 salicylic acid ointment, 22 and salicylic acid liquid. 23 Cook and Cook 24 have used a solution of 40% TCA in combination with 70% glycolic acid to successfully treat irregular pigmentation of nonfacial skin, including solar lentigines.…”
Section: Chemical Peelsmentioning
confidence: 99%
“…Following the pioneering work of Van Scott and Yu on the effects of alpha hydroxy acids [53], these agents were popularized as peeling agents for photodamage [54,55,56]. Moy et al [55], in a mini pig model showed that application of 50 and 70% glycolic acid was comparable to TCA 50% in stimulating collagen production.…”
Section: Superficial Peeling Agentsmentioning
confidence: 99%